ПРОГРАММА ВНЕАУДИТОРНЫХ ЗАНЯТИЙ В ПЕДАГОГИЧЕСКОМ ВУЗЕ – СОЦИАЛЬНО-КУЛЬТУРНАЯ КОМПЕТЕНЦИЯ УЧИТЕЛЯ АНГЛИЙСКОГО ЯЗЫКА - Абдимуратова, Н.П. (SCIENCE and SOCIETY, 2017)
The article deals with aims, system and content of extracurricular classes directed to develop and enlarge ideas and knowledge about socio-cultural competence of future teachers of English in pedagogical institutes.